Educational software applied in Chemistry Teaching: Teaching resources that enhance the learning process (Research, Society and Development, 2021)
The use of educational software can favor the construction of teaching and learning processes about the Chemistry curricular component, many difficulties are imposed by the decontextualization and abstraction, which is practically omnipresent, in the contents. Thus, this article aims to carry out a bibliographical survey about software applied to the teaching of Chemistry, as resources that enhance the learning process. The study was concentrated in the Google Academic database, where scientific works on the theme of TDICs as allies in the teaching of Chemistry were explored. A filter was performed on the works found in the following sequence: analysis of titles, keywords and later reading of the abstracts, in order to choose the most relevant works for the purposes of preparing this research. Papers that addressed the application of four software were selected, which were considered the most significant and had the greatest impact on the results obtained. PhET Interactive Simulations, LabVirt, ChemSketch and Avogadro softwares offer significant potential impact on the construction of learning, as they reproduce or simulate reality, which is not visible to the eyes, without the aid of this type of tool. And with society becoming more and more dependent on digital resources, it is emphasized how necessary it is for the teaching pedagogical practice to evolve in order to dialogue with students in a language that is interesting and common to them, the digital language. In this sense, the BNCC emphasizes that the development of this language propels scientific thinking in a critical and significant way, favoring the exercise of student autonomy.